PERSONAL AGENCY IN TIME PERSPECTIVE. AN ATTEMPT OF EMPIRICAL STUDY - Manusyan , S. H.; Grigoryan , A. K. (Modern Psychology, 2018)
The article discusses the interrelation between personal agency and time perspective. The problem of human activity has been theorized in its relatedness with attitudes towards life time, while also outlining some aspects of that relation based on analysis of select empirical data. With multi-dimensionality of the concept of agency and difficulty of its empiricizing in mind, we have proposed to study it through three characteristics indicative of sense of agency based on literature review: reflexivity, autonomy and perceived control. We have proposed to group 6 time perspectives as in Zimbardo and Boyd’s model into two – active and passive. Empirical support, as well as statistical adjustment has been found for this grouping. Interrelation between indicators agency and select time perspective types has been confirmed. The analysis concludes with arguing for relevance of psychological investigation into the sense of agency of Armenian youth, and landmarks possible pathways of such research.
Keywords: (sense of) agency; agent; life time; time perspective; active time perspectives; passive time perspectives